Integrating Dance/Movement Therapy in Psychotherapy with the Now Elderly Holocaust Survivor: Using Embodied Knowledge to Touch the Soul. - Shuper Engelhard, Einat; Yael Furlager, Avital (Contemporary Psychoanalysis, 2024)
Individuals who survived the Holocaust as infants are now in their senior years. Having carried lifelong wounds—stemming both from exposure to horrors and from the absence of caregivers to meet basic developmental needs—many of these survivors hold early experiences that remain wordless, stored internally without expression or meaning. Dance/movement psychotherapy encourages patients to engage with embodied knowledge through movement, in parallel with verbal processing of experiences in motion. This integration bridges implicit and explicit realms, supporting the development of a more cohesive sense of self and enabling the processing of early traumatic experiences. Through a case study, we will illustrate interventions that combine bodily focus with verbal symbolism as pathways to growth and tranquility in later life.